Prevalence and Correlation of Hypertension, Obesity and Diabetes Among Adults Visiting Community Based Screening Programs - Bansal, Prerna; Shrestha, Ayasha; Panthi, Srijana (Journal of College of Medical Sciences-Nepal, 2022)
Introduction: According to the World Health Organization, diabetes, hypertension and obesity are one of the top five continuing risk factors for cardiovascular deaths in the world. Hypertension and obesity increase the risk of long-term vascular complications of type 2 diabetes mellitus. This study aims to find the prevalence and correlation of hypertension, obesity and diabetesamong the adults in central part of Nepal. Methods: An analytical cross-sectional study was conducted among 233adults visiting the community based screening programs in Bharatpur-10, Nepal organized by College of Medical Sciences during July 2022 to August 2022. Descriptive analysis was done to find the frequency, percentage and mean.To find the association between continuous variables correlation was used (p-value <0.05). Results: The mean age was 53.71±12.42 years, 60.9% males and 39.1% females. The prevalence of hypertension was found to be 25.7%, obesity was 21.8% and diabetes was 36.5%.The FBS was positively correlated with age, SBP, DBP and BMI. The correlation of FBS with age (p-value 0.05) and SBP (p- value 0.01) was found to be statistically significant. Conclusions: The prevalence of hypertension, obesity and diabetes were found to be high both in male and female adults visiting the community based screening programs. Fasting blood glucose was found to be positively correlated with age, body mass index, systolic and diastolic blood pressure measurements of the patient. Thus, level of fasting blood sugar level increases with increasing age, increasing body mass index, increasing systolic and diastolic blood pressure levels of the patient.